Dairy cattle breeding research - background, proposals and preliminary results - Thorpe, W.R. (International Livestock Centre for Africa, 1990)
Presents the background to a research programme on the evaluation of the comparative health and performance of dairy cattle genotypes for smallholder production in the subhumid tropics. Outlines the current breeding studies and gives results from the first of the studies. Includes data on genetic differences and heterosis for dairy production traits in crosses between Bos taurus and Bos indicus cattle. Examines the proportion of heterosis with varying proportions of Bos taurs and Bos indicus, performance of Friesian Brown Swiss and Jersey F1 crosses with Bos indicus, traits of 67 percent Sahiwal 33 percent sahiwal - 67 percent Ayrshire breeding groups at Kilifi plantation. Gives examples of dairy production systems and levels in the Kenya coastal area. Looks into reproductive and lactation traits of five genotypes in three breeding systems, milk yield for five genotypes, and performance of Ayrshire/Sahiwal crosses in two contrasting environments.